2023
DOI: 10.1186/s12864-023-09115-9
|View full text |Cite|
|
Sign up to set email alerts
|

Complete chloroplast genomes provide insights into evolution and phylogeny of Zingiber (Zingiberaceae)

Abstract: Background The genus Zingiber of the Zingiberaceae is distributed in tropical, subtropical, and in Far East Asia. This genus contains about 100–150 species, with many species valued as important agricultural, medicinal and horticultural resources. However, genomic resources and suitable molecular markers for species identification are currently sparse. Results We conducted comparative genomics and phylogenetic analyses on Zingiber species. The Zing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 78 publications
10
13
0
Order By: Relevance
“…In this study, no substantial differences were observed in the total number of genes, protein-coding genes, tRNAs, or rRNAs between C. comosa and C. latifolia . Similar findings were observed in other plant species in Zingiberaceae [ 32 , 33 , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ]. The frequencies of codon usage for each triplet nucleotide sequence encoding a specific amino acid were analyzed.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, no substantial differences were observed in the total number of genes, protein-coding genes, tRNAs, or rRNAs between C. comosa and C. latifolia . Similar findings were observed in other plant species in Zingiberaceae [ 32 , 33 , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ]. The frequencies of codon usage for each triplet nucleotide sequence encoding a specific amino acid were analyzed.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we compared the cp genome structure of ve Clematis species using mVISTA (using Clematis fruticosa as a reference) and found that the non-coding region was more prone to mutations than the coding region. Furthermore, the variation in the SC region was higher than that in the IR region, which is similar to the results of previous plant studies [25,51,53]. psbA-atpA, atpI-rpoC2, rpoB-psbD, psbE-petG, clpP, and rpoC2 were the most highly variable regions detected in C. nannophylla.…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllasupporting
confidence: 90%
“…Lastly, ycf1 encodes unknown proteins and is competent in identification at genus and species level of orchids [ 46 ]. Recent studies have revealed that these eight genes with positive selection in flowering plants are common [ 27 31 , 33 , 35 , 47 , 48 ]. For example, ndhF has been reported as a positive selection in the Aroideae species [ 30 ]; clpP and ycf1 have been reported as positive selections in the Polystachya species [ 31 ]; ndhA and clpP have been reported as positive selections in the Hoya species [ 35 ]; ndhA , clpP , rps12 and ycf1 have been reported as positive selections in the Zingiber species [ 33 , 47 ]; and cemA , clpP , ndhF , petB , rps12 and ycf1 have been reported as positive selections in the Dalbergia species [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that these eight genes with positive selection in flowering plants are common [ 27 31 , 33 , 35 , 47 , 48 ]. For example, ndhF has been reported as a positive selection in the Aroideae species [ 30 ]; clpP and ycf1 have been reported as positive selections in the Polystachya species [ 31 ]; ndhA and clpP have been reported as positive selections in the Hoya species [ 35 ]; ndhA , clpP , rps12 and ycf1 have been reported as positive selections in the Zingiber species [ 33 , 47 ]; and cemA , clpP , ndhF , petB , rps12 and ycf1 have been reported as positive selections in the Dalbergia species [ 48 ]. Among the analyzed species of Costaceae, they possessed diversity of ecological habitats, such as shade under the woods, forest margins, moist places in valleys, roadsides and ditch sides [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%